Synthesis of Main Chain Polymeric Benzophenone Photoinitiator via Thiol-ene Click Chemistry and Its Use in Free Radical Polymerization - Temel, Gokhan; Karaca, Nurcan; Arsu, Nergis (WILEY-BLACKWELL, 2010)
Main chain polymeric benzophenone photoinitiator (PBP) was synthesized by using Thiol-ene Click Chemistry and characterized with (1)H NMR, FTIR, UV, and phosphorescence spectroscopies. PBP as a polymeric photoinitiator presented excellent absorption properties (epsilon(294) = 28,300 mol(-1) L(-1) cm(-1)) compared to the molecular initiator BP (epsilon(252) = 16,600 mol(-1) L(-1) cm(-1)). The triplet energy of PBP was obtained from the phosphorescence measurement in 2-methyl tetrahydrofurane at 77 K as 298.3 kJ/mol and according to phosphorescence lifetime, the lowest triplet state of PBP has an n-pi* nature. Triplet-triplet absorption spectrum of PBP at 550 nm following laser excitation (355 nm) were recorded and triplet lifetime of PBP was found as 250 ns. The photoinitiation efficiency of PBP was determined for the polymerization of Hexanedioldiacrylate (HDDA) with PBP and BP in the presence of a coinitiator namely, N-methyldiethanolamine (MDEA) by Photo-DSC. The initiation efficiency of PBP for polymerization of HDDA is much higher than for the formulation consisting of BP. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 48: 5306-5312, 2010
Keywords: benzophenone; click chemistry; photopolymerization; photochemistry; polymeric photoinitiator; radical polymerization; thiol-ene; CE(IV)/HNO3 REDOX SYSTEM; MIDCHAIN MACROPHOTOINITIATOR; TELECHELIC POLYMERS; COUPLING PROCESSES; POLYURETHANE; CYCLOADDITIONS; COMBINATION; COPOLYMERS; DENDRIMERS; Polymer Science